PRIVATISASI, KAPITALISME DAN NEGARA DALAM PELAYANAN KESEHATAN (SUATU STUDI PERUBAHAN SOSIAL DALAM INDUSTRI KESEHATAN) - Iwan Gardono Sujatmiko (LIPI Press, 2010)
This article analyzes the health service conducted by the state along with private sectors and it illustrates the positive roles of public health agencies. A more active role of state supported by tax and priority in state budget will result in social inclusion and access for the majority in the lower strata. On the other hand, privatization of state hospitals will weaken state’s capacity in providing health services. The increased role of domestic and foreign private sectors within health industry must be controlled in order to protect patients and to create a fair competition in the health service market. This complex change calls for a strong accountability of state institutions as well as health service providers and practitioners, especially doctors as it requires a more critical mass media and active society. It needs a paradigm that perceives patients as citizens with their constitutional rights supported by their members of legislature in their constituencies, not merely as consumers in uncontrolled market. Keywords: Public Health, Privatization, Capitalism, Social Inclusion, Social Change